2015
DOI: 10.1097/md.0000000000002184
|View full text |Cite
|
Sign up to set email alerts
|

Opsonic and Antibody Responses to Pneumococcal Polysaccharide in Rheumatoid Arthritis Patients Receiving Golimumab Plus Methotrexate

Abstract: Vaccination against Streptococcus pneumoniae is recommended for rheumatoid arthritis (RA) patients receiving immunosuppressive treatments. The objective of this study was to evaluate the humoral response to 23-valent pneumococcal polysaccharide vaccination (PPSV23) in RA patients receiving methotrexate (MTX) alone or in combination with a tumor necrosis factor inhibitor, golimumab (GOM).PPSV23 was given to 114 RA patients, who were classified into three groups: RA control (n = 35), MTX alone (n = 55), and GOM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(33 reference statements)
1
10
0
3
Order By: Relevance
“…In this cohort, a direct correlation was shown between the postvaccination levels of antipneumococcal antibodies and the risk of pneumococcal infections: more robust antibody responses after vaccination with PCV7 were associated with lower risk of serious pneumococcal infections 123. The humoral immunogenicity and safety of PPSV23 were demonstrated in RA,76 81 109 112 113 119 124 SLE,116 125 134 and, to a limited extent, in SpA and other rheumatic diseases 115. The long-term immunogenicity of PPSV23 was evaluated in two studies in patients with RA, treated with MTX121 and biologics 130.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In this cohort, a direct correlation was shown between the postvaccination levels of antipneumococcal antibodies and the risk of pneumococcal infections: more robust antibody responses after vaccination with PCV7 were associated with lower risk of serious pneumococcal infections 123. The humoral immunogenicity and safety of PPSV23 were demonstrated in RA,76 81 109 112 113 119 124 SLE,116 125 134 and, to a limited extent, in SpA and other rheumatic diseases 115. The long-term immunogenicity of PPSV23 was evaluated in two studies in patients with RA, treated with MTX121 and biologics 130.…”
Section: Resultsmentioning
confidence: 98%
“…From the previous recommendations and up to August 2018, 34 studies53 76 81 83 84 105–133 and two meta-analyses45 77 have been published on the efficacy, immunogenicity and safety of PPSV23 and the conjugated vaccines PCV7 and PCV13, including evaluation of a combined strategy (tables 7 and 8). 106 128 133…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a retrospective study on the long-term effect of PPSV23 in RA patients treated with MTX showed a relative risk of 9.7 to develop pneumonia in non-vaccinated patients 124. The humoral immunogenicity and safety of the PPSV23 has been demonstrated in RA,64 87 125–129 SLE,130–132 and to a limited extent in SpA and others 133. The long-term immunogenicity of PPSV23 has been evaluated in two studies, in RA patients treated with MTX124 and biologics, respectively 134.…”
Section: Resultsmentioning
confidence: 99%
“…При этом Т-независимый гуморальный ответ (в том числе на ППВ-23) блокируется в значительно меньшей степени [49]. Отсутствие значимого ингибирующего влияния иФНОα на иммуногенность ППВ-23 у больных РА подтверждено другими авторами [50], в том числе в нашей работе [51]. Французские исследователи [52] показали, что последовательное применение ПКВ-13 и ППВ-23 безопасно у больных СКВ, но не дает преимуществ в иммуногенности по сравнению с таковой при назначении ППВ-23 в отдельности.…”
Section: рекомендации по вакцинации взрослых больных иврзunclassified